Investment in Relationship-Specific Assets: Does Finance Matter? - Martin Strieborny; Madina Kukenova (Lund University, School of Economics and Management, Department of Economics, 2013)
Existing literature highlights opportunistic behavior as the main reason why rational agents underinvest in relationship-specific assets (the hold-up problem). However, a supplier would also be reluctant to undertake relationship-specific investment if she cannot observe financial stability or planning horizon of a buyer. By combining insights from research on relationship-specific investment and signaling role of financial intermediaries, we argue that a strong banking sector can alleviate these information asymmetries between buyers and suppliers. We empirically confirm this hypothesis by showing that industries dependent on relationship-specific investment from their suppliers grow disproportionately faster in countries with a strong banking sector.
Keywords: G21; O16; O40; 330; …nancial development; relationship-speci…c investment; growth